Pengaruh Model Pembelajaran Discovery Learning Terhadap Kemampuan Literasi Dan Berpikir Tingkat Tinggi Siswa - Agazi, Muhammad Gali; Purnamasari, Hetty; Hatip, Ahmad (Peneliti.net, 2024)
By using the Team Games Tournament learning model, it is hoped that learning activities will be able to have a positive impact on cooperation and physical fitness of students in elementary schools. Thus, researchers are interested in examining the influence of the Team Games Tournament learning model on student cooperation and fitness. The objectives of this research include: 1) knowing the influence of the Team Games Tournament Learning Model on Student Collaboration in Class III Volleyball Games at UPTD SDN Ujung Piring Bangkalan, and 2) knowing the influence of the Team Games Tournament Learning Model on Students' Physical Fitness in Class III Volleyball Games UPTD SDN Ujung Piring Bangkalan. This research is quantitative research and uses an experimental research design. The instruments used to collect data were student cooperation and physical fitness questionnaire sheets. The research data was analyzed using the paired sample t test analysis technique and produced research conclusions, namely: 1) There is an influence of the Team Games Tournament learning model on student collaboration in class III volleyball games at UPTD SDN Ujung Piring Bangkalan, and 2) There is an influence of the Team Games learning model Tournament on Students' Physical Fitness in Class III Volleyball Games at UPTD SDN Ujung Piring Bangkalan.